2023
DOI: 10.1007/s11240-022-02441-y
|View full text |Cite
|
Sign up to set email alerts
|

Micropropagation of Brassavola nodosa (L.) Lindl. using SETIS™ bioreactor

Abstract: Brassavola nodosa (L.) Lindl. is a tropical epiphytic orchid showing characteristics of interest for the ornamental nursery industry. However, problems with traditional propagation methods limit the development of a large-scale commercial production system. In addition, this species is considered endangered due to the reduction in population caused by habitat destruction, climate change and overcollection from native areas. The use of micropropagation has been investigated for this species, and the use of liqu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
1
6
1
Order By: Relevance
“…Alister et al [2005] indicated that the use of the temporary immersion bioreactor system RITA® resulted in enhanced shoot elongation in Eucalyptus clones compared to semi-solid media. On the other hand, Vendrame et al [2023] research in Brassavola nodosa (L.) indicated that there were no significant differences in shoot length and leaf number between culture systems, including SETIS™ temporary immersion bioreactors and conventional semi-solid methods, which was consistent with the findings of Kaçar et al [2020].…”
Section: Resultssupporting
confidence: 88%
“…Alister et al [2005] indicated that the use of the temporary immersion bioreactor system RITA® resulted in enhanced shoot elongation in Eucalyptus clones compared to semi-solid media. On the other hand, Vendrame et al [2023] research in Brassavola nodosa (L.) indicated that there were no significant differences in shoot length and leaf number between culture systems, including SETIS™ temporary immersion bioreactors and conventional semi-solid methods, which was consistent with the findings of Kaçar et al [2020].…”
Section: Resultssupporting
confidence: 88%
“…In addition, an increase in chlorophyll synthesis has also been reported by using TIS in the micropropagation of A. andreanum, and the relative chlorophyll content was significantly higher for Brassavola nodosa (L.) Lindl. plantlets produced in TIS bioreactors as compared to those from a semisolid medium [25]. In this experiment, however, in temporary immersion bioreactors, the relative chlorophyll content of the leaves of the explants was significantly lower than that of the control using the traditional method.…”
Section: Discussioncontrasting
confidence: 58%
“…The extraction of shoots with forceps from in vitro culture containers, as well as from TIS bioreactors, followed by arranging them on sterile surfaces in order to divide them with the help of surgical scalpels and their subsequent introduction into new culture containers, a process known as subculturing in the conventional in vitro culture process, is time-consuming and represents a significant portion the hand labor involved in most in vitro plant culture processes. The components of the actual GreenTray ® TIS bioreactor described herein, which is a further evolution of the ones presented in the past [31,32], make it significantly improved and versatile compared to other commercial TIS bioreactors, such as RITA ® , Matis ® , Plantform TM , SETIS TM [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17], or the TIS developed by several in vitro plant culture laboratories oriented to solve particular propagation objectives for diverse plant species [18][19][20][21][22][23][24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Temporary immersion system (TIS) bioreactors have been developed over recent decades to favor plantlet or shoot development. The best-known commercial ones are RITA ® , its bigger version Matis ® [1][2][3][4][5][6][7], Plantform TM [8][9][10][11][12][13][14], and SETIS TM [15][16][17]. In addition, there are several other TISs developed for particular purposes by in vitro plant culture laboratories [18][19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%